Implicit Viscosity Iterative Approximation of Fixed Points for Asymptotically Nonexpansive Semigroups - ZHANG Shuyi; NIE Hui (Nantong Daxue xuebao. Ziran kexue ban)
This study aims to introduce a new implicit viscosity iterative algorithm for asymptotically nonexpansive semigroup pairs. The strong convergence theorem of implicit viscosity iterative sequences for asymptotically nonexpansive semigroup pairs with fixed points in Hilbert spaces is established under certain conditions. The results promote and improve the relevant results in some references.